Pengaruh Pinjaman Online Terhadap Stabilitas Keuangan Rumah Tangga - Auliani, Nasywa; Salzabil, Azizah Zalfaa; Rahma, Agisna (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The advancement of financial technology (fintech) has become a major driver of the increasing use of online lending (pinjol) services in Indonesia. Easy access and fast processes have made pinjol an attractive financing option for the public. However, the use of online loans without adequate planning and understanding can negatively affect household financial stability. This study aims to evaluate the extent to which online lending impacts household financial conditions, particularly in terms of debt management, daily expenses, and saving capacity. The research was conducted through literature review, the use of secondary data from OJK (Financial Services Authority) and BPS (Statistics Indonesia), and a descriptive quantitative analysis approach. The findings show that the surge in online loan usage, when not accompanied by sufficient financial literacy, has the potential to cause financial imbalances in households, such as loan defaults, emotional stress, and decreased purchasing power. Therefore, increasing financial education and enforcing stricter regulations are necessary to ensure consumer protection.